a) 3x[-9+4x(4+5)]:(+9-2-12)= b) (-2)x[(-12):(-4+9-2)-(3-5 )]=
Răspunsuri la întrebare
Răspuns de
0
a) 3x[-9+4x(4+5)]:(+9-2-12) = -16.2
3x(-9+36):(-5) = -16.2
3x27:(-6)= -16.2
81:(-5)= -16.2
b) (-2)x[(-12):(-4+9-2)-(3-5)]= 4
(-2)x[(-12):3-(-2)]= 4
(-2)x[(-4)-(-2)= 4
(-2)x(-2)= 4
Sper ca te-am ajutat ^.^
3x(-9+36):(-5) = -16.2
3x27:(-6)= -16.2
81:(-5)= -16.2
b) (-2)x[(-12):(-4+9-2)-(3-5)]= 4
(-2)x[(-12):3-(-2)]= 4
(-2)x[(-4)-(-2)= 4
(-2)x(-2)= 4
Sper ca te-am ajutat ^.^
denizdrew:
Ms
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă